Dampak Pasar Kripto Terhadap Kinerja Pasar Saham di Indonesia - Yari Yaldi; Syahrizal Chalil; Diana Hasyim (Global Leadership Organizational Research in Management, 2024)
This study aims to analyze the effect of the cryptocurrency market on the performance stock market. It considers IDX Composite as dependent variable while monthly price and volume Bicoin as independent variables and monthly inflation and the Bank Indonesia benchmark interest rate (BI Rate) as controlled variables from January 2018 to May 2024. Applying multiple linear regression model. The results of the study indicate that Bitcoin price has positive impact on the performance of stock market while it notices a negative impact on the same of the volume. Both Inflation and BI Rate also has positive impact on the performance stock. This research provides empirical evidence of the relationship between the cryptocurrency market and the stock market in Indonesia, as well as providing implications for investors, regulators, and academics.